Cell wall degrading enzymes in host-pathogen interaction of Fusarium wilt of chickpea: Inhibitory effects of phenolic compounds - and M. PARAMESWARAN, M.K. MANDAVIA, H.P. GAJERA, J.H. ANDHARIA,* R.R. KHANDAR (Indian Phytopathology, 2002)
Studies were conducted on polymethyl galacturonase (PMG) and cellulase levels in chickpea (Cicer arietinum) cvs. JCP-27 (wilt resistant) and JG-62 (wilt susceptible) grown in a wilt (Fusarium oxysporum f.sp. ciceris) infected plot at Jaganath, Gujarat, India. In vitro assays were conducted to assess production of enzymes in the presence of phenolic compounds. Results indicated that the fungus was present in all tissues of both varieties (except for leaf tissue of the resistant variety) 18 days after planting (DAP). Symptoms were severe 22 DAP, at which time root and stem tissue of the susceptible cultivar supported profuse fungal growth compared with the resistant cultivar. Viscometric assays indicated little or no PMG activity in uninfected tissue, but increased activity with fungal growth in the susceptible cultivar, and enzyme levels were highest in stem and leaf tissues. Although fungal growth occurred in the resistant cultivar, there was little change in PMG activity, and none was recorded in leaf tissue. Cellulase levels were low at all disease stages in both cultivars, except in susceptible plants with advanced disease symptoms.